A Solid‐State Electrochemiluminescence Sensor Based on Novel Two‐Dimensional Ti3C2 MXene. Issue 10 (18th May 2021) - Xing, Huanhuan; Xia, Hongyin; Fan, Yongchao; Xue, Yuan; Peng, Chao; Ren, Jiangtao; Li, Jing; Wang, Erkang
Abstract: Herein, highly conductive MXene‐Ti3 C2 was employed as effective nanocarriers for anchoring electrochemiluminescence (ECL) luminophore of Ru(bpy)3 2+ (Ti3 C2 −Ru). Different from the previous work, the Ti3 C2 −Ru composite was achieved in several seconds due to the electrostatic interaction between positively charged Ru(bpy)3 2+ and negatively charged Ti3 C2 . A series of characterizations indicated the successful formation of Ti3 C2 −Ru. Then, the solid‐state ECL platform was constructed with the assistance of membrane material, Nafion. The introduction of Ti3 C2 with large surface area provided a rapid strategy for capturing luminophore of Ru(bpy)3 2+ and endowed the solid‐state platform with good electron transfer capacity owing to the super conductivity. Based on the stable loading of Ru(bpy)3 2+, the as‐designed platform was successfully used for the analysis of lidocaine and the satisfied analytical results were obtained in human plasma. More importantly, the proposed approach not only enriched the application of Ti3 C2 in the sensing field, but also shed light on the label‐free ECL bioanalysis. Abstract : Quick and easy : A Ti3 C2 −Ru composite was obtained by simple two‐step mechanical treatment in several seconds and the solid‐state ECL sensor based on the Ti3 C2 −Ru composite for lidocaine was successfully constructed, holding great promising for various targets analysis.